Nivel de ventas de las cocinas de inducción frente a las cocinas tradicionales en el almacén Expogar - Briones González, Melany Anahel (2020)
The research work was carried out to analyze the sales levels of induction cookers and traditional cookers in the Expogar warehouse and to identify how it affects the warehouse during the year 2015 to the present, the objective of this research is to know what the factors are and the causes that cause the decrease in sales in the warehouse during this period; In addition, the advantages and disadvantages of using these kitchens for the population are detailed. It also specifies how sales levels affect the company. The Expogar warehouse is located on the streets May 27 between June 5 and García Moreno, its business activity is the sale and purchase of household items such as appliances, furniture, wardrobes, consoles, among others; in order to satisfy the customer. In this investigation, two data collection techniques were considered: the survey that was directed at some of the clients, and the interview that was directed at the owner and manager of the warehouse. These collection techniques helped to obtain information on the factors and causes that occurred during that period and affected sales in the warehouse